Characterization of carbon nanolayer of optical fibers via near-field Raman spectroscopy - S.V. Saparina; S.S. Kharintsev (Учёные записки Казанского университета: Серия Физико-математические науки)
Optical fibers are commonly used for distributed sensing in oil wells. In typical down-hole environment fibers are subjected to a significant mechanical stress at high temperatures and pressures. To prevent mechanical destruction of the fiber surface, optical fibers are coated with a thin carbon layer. Although the considerable advance has been achieved in coating technologies, there is still no full understanding of the causes of microscopic cracks on the surface of the protective layer, which contribute to hydrogen penetration into the fiber core. In this work, we have characterized the surface structure of hermetic carbon coatings of different thicknesses, from 1 to 100 nm, using atomic force microscopy (AFM) and far- and near-field Raman spectroscopy. Based on the obtained results, we have determined the optimal composition, thickness, and morphology of the carbon layer that ensure the best hermetic properties of the layer with sufficient mechanical strength. In addition, the formation of carbon allotropes – nanotubes, graphene, soot, and fullerenes – in the protecting carbon layer has been revealed by near-field Raman spectroscopy. These allotropes can serve as additional pathways for diffusion of molecular hydrogen through the carbon layer onto silica glass.